PENINGKATAN KOMPETENSI MENEMUKAN INFORMASI PADA BUKU TELEPON MELALUI MODEL PEMBELAJARAN KOOPERATIF TEAMS GAMES TOURNAMENT PADA SISWA KELAS VIII PUSAT KEGIATAN BELAJAR MASYARAKAT SAHABAT KARANGANYAR - Muhammad Abid Mukhlisin; Budhi Setiawan; Sri Hastuti (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
The research was aimed to know whether cooperative learning model with teams games tournament type could improve both process and the scanning reading competention on finding  information from phone book. This research subjects was the eighth grade students of PKBM Sahabat Karanganyar in academic year of 2016/2017. Data were collected by document analysis, observation, and interview. The data validity was tested by data triangulation technique. Data was analyzed by comparative descriptive technique. This research procedure consists of: (1) the planning; (2) the act of learning; (3) observation; and (4) analysis and reflection. The result showed that there were improvement of process and scanning reading competention on finding information from phone book through cooperative learning model with teams games tournament type in the eighth grade students of PKBM Sahabat Karanganyar in academic year of 2016/2017.